Influence of physical development on start and countermovement jump performance in adolescent sprint athletes - Aerenhouts, D.; Debaere, S.; Hagman, F.; Van Gheluwe, B.; Delecluse, C.; Clarys, P. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of the present study was to describe the effect of physical changes during adolescence on sprint start and countermovement jump (CMJ) performance. Methods: Twenty-eight girls and 25 boys (15.0±1.6 and 14.7±1.9 years at start respectively) were measured twice with a one year interval. Anthropometric data allowed skeletal muscle mass (SMM) estimation. Athletes performed a 10m sprint tracked from behind by a laser sensor, with starting blocks measuring propulsion forces. CMJ`s were performed on a Kistler force plate. Results: Between the two measurement occasions both genders increased in body height, weight and SMM. In girls and boys, impulse during the push-off, block leaving velocity and times at 5 and 10 m improved significantly. In both genders CMJ absolute power increased but not power.kg-1. Only in boys a higher CMJ was registered on occasion 2. For both genders on both occasions, impulse during the push-off correlated with body weight, SMM and CMJ power (r from .46 to .84), and in boys also with CMJ height and CMJ power/kg (r from 0.43 to 0.76). Boys showed CMJ height and power to correlate with 5 and 10 m times (r from -0.42 to -0.79) and with block leaving velocity, however only on the first data collection (r=0.61 and 0.59, respectively). Conclusion: Sprint start performance is only partly related to muscular development and CMJ could predict start performance in boys only. Sprint start and CMJ rely on technical skills and, therefore, increasing muscularity should be accompanied with sufficient specific training to allow an optimal transfer to start performance.